A quantitative study of the mediating role of self-esteem in the relationship between social support and subjective well-being in middle adulthood - Phandywijaya, Saras Ayudhia Maharani Putri; Siska Adinda Prabowo Putri; I. Rheny Arum Permitasari (Universitas Ahmad Dahlan, 2025)
Subjective well-being is a crucial indicator of an individual's quality of life, particularly during middle adulthood a developmental stage marked by increased vulnerability to psychological stress due to life transitions. This study aims to examine the effect of social support on subjective well-being among middle-aged adults, employing a mediation model in which self-esteem functions as the mediating variable. Utilizing a quantitative approach with path analysis, data were collected from 384 middle-aged individuals aged 40–60 years residing in DKI Jakarta, selected through purposive sampling. The findings reveal that social support has a significant impact on subjective well-being, both directly and indirectly through the mediation of self-esteem. These results underscore the critical role of self-esteem in mediating the relationship between social support and subjective well-being during middle adulthood.